Studi Karakteristik Petani Desa Tulungrejo dalam Mendukung Pengembangan Agrowisata “Bon Deso” - Pravasta Wahyu Satriawan; Muhammad Saikhu; Rika Despita; Budi Sawitri (Jurnal KIRANA, 2021)
This study aims to study the support characteristics of Tulungrejo Village Farmers for the development of "Bon Deso" Agrotourism which is being developed by the Tulungrejo Village Government. This research was conducted in Tulungrejo Village, Kec. Bumiaji, Batu City with the method of determining the location that is purposive. The population of this study were all members of the farmer group in Tulungrejo Village as many as 646 farmers, while for the sample of this study as many as 87 farmers were obtained using the Slovin formula and the determination was made using simple random sampling. This research method is a survey with data collection techniques of observation, interviews, and research instruments and data analysis techniques using descriptive statistics. The results showed that the description of farmers in Tulungrejo Village were mostly 36-45 years old with an average length of formal education of 6-9 years which was equivalent to elementary-junior high school education. Non-formal education also contributes to understanding the development of agro-tourism is counseling. The average farmer owns an area of ​​0.01-1.21 ha with farming experience 18-30 years. Income level Rp. 700,000 – Rp. 7,100,000 with a predominant livelihood as farmers. Such conditions are very possible for agro-tourism managers to collaborate with farmers to contribute to agro-tourism as a means for them to improve their welfare. Key words: Agrotourism, Characteristics, Farmers